Dry Needling in Overhead Athletes with Myofascial Shoulder Pain: A Systematic Review - Andrea Demeco; Alessandro de Sire; Antonello Salerno; Nicola Marotta; Stefano Palermi; Antonio Frizziero; Cosimo Costantino (MDPI AG, 2024)
The treatment of myofascial pain in athletes requires a set of rehabilitation techniques that aim to be effective quickly. In this context, dry needling (DNY) has shown interesting results due to its ability to reduce pain in the short term. Thus, the aim of this study was to investigate the role of DNY in managing myofascial shoulder pain in overhead athletes. PubMed, Scopus and Web of Science were screened up to March 2024, to identify studies that met the following inclusion criteria: overhead athletes with shoulder pain with a DNY approach for myofascial trigger points (MTrPs), RCT, case-control study, feasibility study as the study design. Exclusion criteria were studies that did not include athletes, studies that did not focus on the treatment of MTrPs with DNY, other reviews, no full-text availability and papers written in a language other than English. Out of 399 articles, 165 were excluded as duplicates. Of the 234 articles screened, only 6 articles met the inclusion criteria. A total of 6 studies were included in the systematic review. Initial results showed that DNY improved pain rapidly and in the short term; however, there is still no consensus on the minimum number and the interval between treatments. Major findings reported a rapid potential decrease in perceived pain, shoulder disability and an increase in muscle strength; in this scenario, DNY might be a valid solution in a sports rehabilitation setting.